Cognitive abilities and theory of mind in explaining communicative-pragmatic disorders in patients with schizophrenia. (February 2018) - Parola, Alberto; Berardinelli, Laura; Bosco, Francesca M.
Abstract: Patients with schizophrenia usually show an impairment in their communicative-pragmatic performance; they also have difficulties in cognitive functioning and Theory of Mind (ToM). In the literature it has been proposed that ToM and cognitive deficits have a role in explaining the communicative-pragmatic difficulties of patients with schizophrenia. However, the exact interplay of these functions is still not completely clear. The present research investigates the relationship between communicative-pragmatic, ToM and cognitive impairments (i.e. general intelligence, selective attention, speed processing and EF -working memory, inhibition and flexibility-) in a sample of 26 individuals with schizophrenia and matched controls. The linguistic and extralinguistic scales of the Assessment Battery of Communication (ABaCo), and a series of ToM and cognitive tasks were administered to patients and healthy controls. The results showed that individuals with schizophrenia performed less well than controls in all the tasks investigated. However, a hierarchical regression analysis showed that only ToM, and not cognitive functions, seems to be a predictive variable of patients' performance. Finally, a Fisher's exact test showed that there was not a stable significant relationship between ToM or EF and pragmatic impairment. Highlights: Patients' difficulty in dealing with, direct speech acts, irony and deceits. Individuals' with schizophrenia difficulties in pragmatic comprehension and production. Increasing difficulty in managing sincere, deceitful, ironic communicative acts. Examining the relation between pragmatic, cognitive and ToM skills in schizophrenia. Limited role of ToM and executive function in explaining patients' pragmatic performance.